Resin production in Turkiye and the role of civil forestry - Yaşar, Mesut; Çağlar, Lale; Tez, Hüda; Karademir, Arif (Bursa Technical University, 2024)
Resin, despite being a highly significant non-timber forest product, is unfortunately underutilized in our country. Resin is a plant extract produced primarily by coniferous trees for defensive purposes and in response to injuries. Particularly, the Mediterranean, Aegean, and Marmara regions are rich in coniferous tree species with high resin content. Among these species, national trees such as the Turkish Red pine and the high-resin-producing Maritime pine forests are noteworthy. Although valuable scientific research on resin has been conducted in our country, the topic has yet to cross a critical threshold and become a sustainable sector. This study reviews the methods of resin production in general and examines existing research on the subject within the country. It provides a detailed eva-luation of the necessary steps to increase resin production, convert it into value-added products, utilize it in industry, develop branding, and completely end dependence on foreign sources. To establish a national, local, and innovati-ve economy in the resin market, long- term projects and collaborations involving public, industrial, and academic sectors are needed. The topic is discussed particularly in the context of civil, industrial, and functional forestry.

Reçine, çok önemli bir odun dışı orman ürünü olmasına rağmen ne yazık ki ülkemizde mevcut potansiyeli değer-lendirilememektedir. Bilindiği üzere, ibreli ağaçlar tarafından genelde savunma amaçlı ve yaralanmalara karşı üretilen bitki özütüne reçine denmektedir. Özellikle Akdeniz, Ege ve Marmara Bölgesi reçine oranı yüksek olan ibreli ağaç türlerimiz açısından oldukça zengin bir varlığa sahiptir. Bu türler içerisinde ulusal ağaçlarımızdan olan özellik-le kızılçam ve yüksek reçine salgılayan sahil çam ormanları dikkat çekmektedir. Reçine konusunda ülkemizde çok değerli bilimsel çalışmalar yapılmıştır, ancak konu henüz kritik eşiği aşamamış ve sürdürülebilir sektör haline ge-çememiştir. Bu çalışmada, genel olarak reçine üretim metotları değerlendirilerek, ülkemizde konu hakkında yapıl-mış çalışmalar gözden geçirilmiştir. Reçine üretiminin artması, katma değerli ürünlere dönüştürülmesi, sanayide değerlendirilmesi, markalaşma ve bu konuda dışa bağımlılığın tamamen sonlandırılması için yapılması gerekenler detaylı olarak değerlendirilmiştir. Reçine piyasasında milli, yerli ve inovatif bir ekonomi oluşturulabilmesi için özellikle kamu, sanayi ve üniversite iş birliğinde uzun soluklu projeler ve çalışmalar yapılmasına ihtiyaç duyulmak-tadır. Konu, özellikle sivil, endüstriyel ve fonksiyonel ormancılık noktasında tartışılmıştır.
Türkiye’de reçine üretimi ve sivil ormancılığın rolü
Keywords: Nonwood Forest Products Industry; Odun Dışı Orman Ürünleri Endüstrisi [EN] Forest Industry Engineering (Other); Orman Endüstri Mühendisliği (Diğer) [EN] Forestry Biomass and Bioproducts; Orman Biyokütlesi ve Biyoürünleri [EN] Forestry Sciences (Other); Ormancılık (Diğer)